Correlation of the Saalian glacial limits in eastern Poland and western Belarus - Marks, Leszek; Pavlovskaya, Irina E. (Quaternary international, 2006)
The Saalian in the Polish–Belarusian cross-border region is represented by a single till in the south and two tills in the north. The Wartanian glacial limit extends roughly from Łuków and Biała Podlaska in eastern Poland through Vysokoye and Kamenets to Bereza in western Belarus. The maximum and recessional limits both show a distinct lobate pattern. The first-rank interlobate zone that separated the Vistula and the Neman lobes coincides with the bedrock elevations at Vysokoye and Kamenets in Belarus. The lobate character of the Wartanian ice margin in eastern Poland and western Belarus suggests its metachroneity over short distances and changing dynamics of the ice body. The latter must have been significantly influenced by the gradual increase in climate continentality, reflected by abundant dead ice and stagnant glacial landforms.